2021
DOI: 10.1097/ju.0000000000002148.06
|View full text |Cite
|
Sign up to set email alerts
|

Lba01-06 randomized Control Trial of Ultrasonic Propulsion to Facilitate Clearance of Chronic Residual Fragments

Abstract: INTRODUCTION AND OBJECTIVE: Erectile dysfunction (ED) treatments are effective and widely available. While it has been previously demonstrated that different races in the United States display varied prevalence of ED it remains uncertain whether treatment-seeking patterns differ by race/ethnicity. In this present study, we examine the relationship between race and erectile dysfunction treatment.METHODS: We performed a retrospective review using Optum's De-identified ClinformaticsÒ Data Mart database. Administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…BWL's short harmonic bursts of ultrasound from a handheld therapy and imaging transducer have been well tolerated with minimal hematuria by awake patients. 9,10 As a precursor to a clinical effectiveness study, the study reported here was designed to directly observe how well BWL fragmented stones and any tissue injury associated with the procedure. As such, we recruited subjects already undergoing ureteroscopy (URS), and while the subjects were anesthetized, we applied 10 minutes of BWL and then used the ureteroscopic video to assess for fragmentation and injury.…”
Section: Study Need and Importancementioning
confidence: 99%
See 2 more Smart Citations
“…BWL's short harmonic bursts of ultrasound from a handheld therapy and imaging transducer have been well tolerated with minimal hematuria by awake patients. 9,10 As a precursor to a clinical effectiveness study, the study reported here was designed to directly observe how well BWL fragmented stones and any tissue injury associated with the procedure. As such, we recruited subjects already undergoing ureteroscopy (URS), and while the subjects were anesthetized, we applied 10 minutes of BWL and then used the ureteroscopic video to assess for fragmentation and injury.…”
Section: Study Need and Importancementioning
confidence: 99%
“…We addressed this unmet need by developing an office-based ultrasound system to image, break and reposition stone fragments to facilitate their natural clearance. 5 A stepwise progression of development and human trials has ensued, 6–10 and this paper reports on the first human feasibility study of our technology called burst wave lithotripsy (BWL) 11 to fragment stones. BWL’s short harmonic bursts of ultrasound from a handheld therapy and imaging transducer have been well tolerated with minimal hematuria by awake patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Independent review of these videos determined that motion ≥ 3 mm had occurred in 18 of 19 kidneys (95%). Data from the most recent clinical study presented at the 2021 meeting of the American Urological Association suggests that ultrasonic propulsion may help relieve pain and accelerate passage of distal ureteral stones [ 35 ], as well as chronic residual fragments [ 36 ]. In the case of this latter study, a subject reported never passing fragments following SWL.…”
Section: Ultrasonic Propulsionmentioning
confidence: 99%
“…A stepwise progression of development and human trials has ensued. [5][6][7][8][9] The present study focused on treating distal and proximal ureteral stones, with emphasis on facilitating passage of distal stones into the bladder and pushing proximal stones back into the kidney. Distal ureteral stones are more common than proximal ureteral stones; both are more common and more reliably visualized with ultrasound than middle ureteral stones.…”
mentioning
confidence: 99%